2022
DOI: 10.1101/2022.11.06.515359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partial Mimicry of the Microtubule Binding of Tau by Its Membrane Binding

Abstract: Tau, as typical of intrinsically disordered proteins (IDPs), binds to multiple targets including microtubules and acidic membranes. The latter two surfaces are both highly negatively charged, raising the prospect of mimicry in their binding by tau. The tau-microtubule complex was recently determined by cryo-EM. Here we used molecular dynamics simulations to characterize the dynamic binding of tau K19 to an acidic membrane. This IDP can be divided into three repeats, each containing an amphipathic helix. The th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Binding studies [20] have shown that the N-WASP BR binds multiple PIP2 molecules and it is the number of basic residues, not the precise sequence, that determines the PIP2 binding affinity, typical of IDP binding to acidic membranes [30]. Structural characterization of IDP-membrane binding, due to its dynamic nature, presents challenges for experimental techniques, but this problem can now be addressed by molecular dynamics (MD) simulations [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Binding studies [20] have shown that the N-WASP BR binds multiple PIP2 molecules and it is the number of basic residues, not the precise sequence, that determines the PIP2 binding affinity, typical of IDP binding to acidic membranes [30]. Structural characterization of IDP-membrane binding, due to its dynamic nature, presents challenges for experimental techniques, but this problem can now be addressed by molecular dynamics (MD) simulations [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%